C/EBP homologous protein–induced loss of intestinal epithelial stemness contributes to bile duct ligation–induced cholestatic liver injury in mice. Issue 4 (19th February 2018) - Liu, Runping; Li, Xiaojiaoyang; Huang, Zhiming; Zhao, Derrick; Ganesh, Bhagyalaxmi Sukka; Lai, Guanhua; Pandak, William M.; Hylemon, Phillip B; Bajaj, Jasmohan S.; Sanyal, Arun J.; Zhou, Huiping
Abstract : Impaired intestinal barrier function promotes the progression of various liver diseases, including cholestatic liver diseases. The close association of primary sclerosing cholangitis (PSC) with inflammatory bowel disease highlights the importance of the gut‐liver axis. It has been reported that bile duct ligation (BDL)‐induced liver fibrosis is significantly reduced in C/EBP homologous protein knockout (CHOP −/− ) mice. However, the underlying mechanisms remain unclear. In the current study, we demonstrate that BDL induces striking and acute hepatic endoplasmic reticulum (ER) stress responses after 1 day, which return to normal after 3 days. No significant hepatocyte apoptosis is detected 7‐14 days following BDL. However, the inflammatory response is significantly increased after 7 days, which is similar to what we found in human PSC liver samples. BDL‐induced loss of stemness in intestinal stem cells (ISCs), disruption of intestinal barrier function, bacterial translocation, activation of hepatic inflammation, M2 macrophage polarization and liver fibrosis are significantly reduced in CHOP −/− mice. In addition, intestinal organoids derived from CHOP −/− mice contain more and longer crypt structures than those from wild‐type (WT) mice, which is consistent with the upregulation of stem cell markers (leucine‐rich repeat‐containing G‐protein‐coupled receptor 5, olfactomedin 4, and SRY [sex determining region Y]‐box 9) and in vivo findings that CHOP −/− mice have longer villi and crypts as compared to WT mice. Similarly, mRNA levels of CD14, interleukin‐1β, tumor necrosis factor‐alpha, and monocyte chemotactic protein‐1 are increased and stem cell proliferation is suppressed in the duodenum of patients with cirrhosis. Conclusion: Activation of ER stress and subsequent loss of stemness of ISCs plays a critical role in BDL‐induced systemic inflammation and cholestatic liver injury. Modulation of the ER stress response represents a potential therapeutic strategy for cholestatic liver diseases as well as other inflammatory diseases. (Hepatology 2018;67:1441‐1457).